Application of Early Mobilization in Reducing Pain in Post Sectio Caesarea Patients in Flamboyant Room Prof. Dr. Margono Soekarjo Hospital - Zulfa Rofiqoh; Siti Haniyah (Viva Medika, 2024)
Sectio Caesarea (SC) or caesarean section is a delivery with an incision procedure in the abdomen and uterus. Post-operative pain will be caused by a caesarean section. Post-operative pain can be reduced with early mobilization as a non-pharmacological technique. This case study aims to determine whether there is any effect of early mobilization in the reduction of the intensity of pain in patients’ post-operation sectio caesarea in the Flamboyan Room of RSUD Prof. Dr. Margono Soekarjo. Qualitative research type with descriptive case study as the research method was used in this study. Total sampling technique with a sample of 1 patient, namely Mrs. I. The data collection method is by interviews and patient medical records. Early mobilization intervention was carried out with an administration time of 15 minutes for 3 days. The results of the case study show a very significant reduction in pain intensity after early mobilization intervention, namely from a scale of 5 to a scale of 3. Early mobilization is important because post-operative pain can be reduced by movement of the body's muscles